TSOL18 vaccine and oxfendazole for control of Taenia solium cysticercosis in pigs: A field trial in endemic areas of Tanzania. - Mwemezi L Kabululu; Helena A Ngowi; James E D Mlangwa; Ernatus M Mkupasi; Uffe C Braae; Angela Colston; Claudia Cordel; Elizabeth J Poole; Kristin Stuke; Maria V Johansen (Public Library of Science (PLoS), 2020)
A field trial was conducted in Tanzania to determine the effectiveness of TSOL18 vaccine used concurrently with oxfendazole (OFZ), and of OFZ alone, on T. solium cysticercosis determined by organ and half carcase dissection of slaughter age pigs. This study followed a quasi-experimental group design. Suitable trial sites were randomly allocated to either treatment group T1 (OFZ treatment alone [30mg/kg, Paranthic 10%]) or T2 (TSOL18 [1ml, Cysvax] plus OFZ). Three 4-monthly treatments were administered to eligible pigs. A random selection of pigs were necropsied at baseline and at endline, 2-3.5 months after the final treatment. Additionally, untreated pigs from T1 and T2 areas were necropsied at endline to provide contemporaneous comparisons with T1 and T2 pigs. Baseline prevalence of viable T. solium cysticerci for T1 was 25.5% (Exact 95% CI: 13.9, 40.3; n = 12/47), and for T2 was 12.0% (CI: 6.4, 20.0; n = 12/100). At endline, prevalence was 2.8% for T1 (CI: 0.1, 14.5, n = 1/36) and 0% for T2 (CI: 0, 4.7, n = 0/77). Among untreated pigs, three had viable cysticerci, one from T1 area (12.5%, CI: 0.3, 52.7; n = 1/8) and two from T2 area (5.7%, CI: 0.7, 19.2, n = 2/35). Fisher's exact test showed significant changes in prevalence from baseline to endline in both groups (T1: p = 0.005, T2: p = 0.001). Firth's penalized Maximum Likelihood method suggested the changes were not significant relative to their controls (T1: p = 0.245, T2: p = 0.076). These findings showed a significant reduction in the prevalence of viable cysticerci from baseline to endline after both interventions. However, the changes could not be definitively attributed to the interventions due, in part, to small numbers of control pigs. Concurrent administration of the TSOL18 and OFZ cleared infection among assessed pigs whereas infection remained after treatment with OFZ only. Further studies including larger sample sizes would be required for more definitive conclusions. A One Health approach is recommended for rapid and sustainable impact.